Impact of Probiotics on Symptom Control in Irritable Bowel Syndrome - Amer, Mariana; Altaf, Shandana; Ullah Kakakhel, Syed Mehtab (Biological and Clinical Sciences Research Journal, 2025)
Irritable Bowel Syndrome (IBS) is a chronic functional gastrointestinal disorder characterized by abdominal pain, bloating, and altered bowel habits, with a significant impact on patients’ quality of life. Intervention. Objective: To evaluate the impact of probiotic supplementation on symptom control and quality of life in patients with IBS. Methods: This observational study was conducted at Naseer Ullah Babar Hospital, Kohat Road, Peshawar, from January 2025 to June 2025. A total of 160 IBS patients fulfilling Rome IV criteria were randomized to receive either a probiotic formulation (containing Lactobacillus and Bifidobacterium species) or a placebo for 12 weeks, in addition to standard lifestyle advice. Results: At week 12, the probiotic group showed a greater reduction in IBS-SSS compared with placebo (122.4 ± 65.2 vs. 82.1 ± 61.8, p = 0.003). A clinical response (defined as a≥50-point reduction in IBS-SSS) was achieved in 68.7% of patients treated with probiotics, compared to 46.2% in the placebo group (p = 0.004). Significant improvements were observed in abdominal pain (48.6% vs. 31.4%, p = 0.01), bloating (44.2% vs. 25.7%, p = 0.008), stool normalization (52.5% vs. 33.7%, p = 0.02), and quality of life (mean improvement 34.6 ± 12.4 vs. 21.8 ± 11.7, p < 0.001). Both interventions were well tolerated, with no serious adverse events. Conclusion: Probiotic supplementation is effective in reducing IBS symptom severity, improving bowel-related outcomes, and enhancing quality of life, with an excellent safety profile. These findings support the role of probiotics as a safe and beneficial adjunct in the management of IBS.